Determinants of Stunting Incidence in ToddlersCross-Sectional Study at Sukomoro Health Center, Magetan Regency, East Java - Tri Wahyuni; Nurlailis Saadah; Suparji; Astin Nur Hanifah; Teta Puji Rahayu (International Journal of Advanced Health Science and Technology, 2026)
Stunting remains a significant public health issue in Indonesia, particularly in regions like Sukomoro, where the prevalence is higher than the national average. This study aims to identify and analyze the factors contributing to stunting in toddlers aged 0-5 years in the Sukomoro Health Center area, Magetan Regency, East Java, to inform effective prevention strategies. A cross-sectional study was conducted involving 300 toddlers selected through simple random sampling from a population of over 1,200. Data were collected via structured interviews and maternal and child health book reviews, followed by statistical analysis using descriptive statistics and ordinal logistic regression. The results revealed that the incidence of stunting was associated with several factors, including maternal health history during pregnancy, especially Chronic Energy Deficiency (KEK), and low maternal education. The regression analysis showed that maternal health significantly increased the risk of stunting in children (B = 0.616, p = 0.026). However, other factors, such as family income, exclusive breastfeeding, and low birth weight, did not show statistically significant associations. This study highlights the importance of maternal health, particularly addressing KEK, as a key determinant in stunting prevention. Effective interventions should focus on improving maternal nutrition before and during pregnancy, alongside strengthening health services and community-based nutrition education.